Effect of crumb rubber gradation on a rubberized cold recycled mixture for road pavements. (15th November 2015) - Pettinari, Matteo; Simone, Andrea
Abstract: Cold recycling technique represents the most environmental friendly solution for pavement rehabilitation nowadays. In fact, this technique allows the use of the highest percentage of reclaimed asphalt avoiding the energy consumption related to aggregates heating required by the traditional hot mix asphalt design. The mix design represents a key phase of the cold mix production. The study of workability and compactability properties combined with a deep laboratory investigation is required. The idea of introducing crumb rubber in the cold mixtures was developed based on the concept of maximizing the valorization of recycled materials together with the goal of achieving high performance. In the present research project, two different gradations of crumb rubber, processed with the traditional grading method, have been adopted for the production of a cold recycled mixture stabilized with bitumen emulsion and cement. The spring-back effects of the rubber particles, which occur after compaction, together with the Indirect Tensile Strength and the Indirect Tensile Stiffness Modulus have been studied. The results show that the gradation of the adopted crumb rubber sensibly affects the compaction and mechanical properties of the cold recycled mixture. Graphical abstract: Highlights: Crumb rubber gradation affects workability and mechanical properties. Spring-back effect decreases with the fineness of the rubber gradation. Spring-back effect is linearly related with the percentage of rubber used. Rubber gradation does not affect the relationship between Indirect Tensile Stiffness Modulus and Indirect Tensile Strength.